2009
DOI: 10.1007/s12262-009-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal diverticulae: reports of two cases with review of literature

Abstract: Introduction Jejunal diverticulosis (JD) is a rare disease of elderly people. Majority of diagnosed individuals are asymptomatic and found incidentally. The disease is clinically signifi cant because of associated potential risk of serious complications. Due to the rarity and variable presentation of this clinical entity, diagnosis is often diffi cult and delayed, resulting in unnecessary morbidity and mortality. Clinical presentations, signs, diagnosis, complications and treatment of JD are discussed through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…in India, We have found seven cases of jejunal diverticulosis reported in India, five of them presented with complications like perforation, gastrointestinal bleeding and intestinal obstruction [3,[5][6][7][8][9][10]. In this regard, a recent cadaveric study of duodenum conducted in South India showed the prevalence of 4.2% for duodenal diverticulosis [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in India, We have found seven cases of jejunal diverticulosis reported in India, five of them presented with complications like perforation, gastrointestinal bleeding and intestinal obstruction [3,[5][6][7][8][9][10]. In this regard, a recent cadaveric study of duodenum conducted in South India showed the prevalence of 4.2% for duodenal diverticulosis [11].…”
Section: Resultsmentioning
confidence: 99%
“…Investigation modalities like CT scan, single or double balloon enteroscopy are useful in diagnosing small bowel disorders [15]. But, they are expensive and cannot be used in an emergency setting [3,5,6]. However, abdominal and chest X-rays can demonstrate perforation.…”
Section: Resultsmentioning
confidence: 99%
“…The surgical findings were matching the radiological report of an uncomplicated diverticulitis without signs of the above mentioned main complications. Thus a thorough abdominal lavage and the insertion of abdominal drains were the only procedures carried out by the surgeons.This approach seemed appropriate to us and is supported by other cases of local and self-limited inflammation [2,[7][8][9].…”
Section: Introductionmentioning
confidence: 83%
“…It is contraindicated in case of perforation or acute diverticulitis to suggest a perforation. [8] Endoscopic procedures, such as double-ballon endoscopy and capsule endoscopy may be helpful in the diagnosis of small bowel diverticula, but have limited utility in emergency setting. Diagnostic laparoscopy is a valuable method and may sometimes prevent unnecessary laparotomies.…”
Section: Case Reportmentioning
confidence: 99%